A dual‐band microstrip antenna using a circular ring and a concentric disk. Issue 3 (29th January 2016) - Gan, Bohua; Zhou, Liang; Zhang, Yao‐Ping; Mao, Jun‐Fa
ABSTRACT: A dual‐band microstrip antenna using a differentially driven annular ring and a single‐ended concentric circular disk is reported. The ring is designed in the TM12 mode at a lower frequency fl and the disk in the TM11 mode at a higher frequency fh . It is found that the mutual loading perturbs the resonant frequencies and thus the outer and inner radii of the ring and the radius of the disk calculated from the cavity models need to be slightly adjusted. More importantly, it is also found that the mutual loading affects the gains and may reduce the gain of the disk antenna substantially. The cavity‐model design formulas to determine the ring and disk dimensions are modified to account for their mutual loading between the ring and disk. It is shown that the differentially driven ring has an improved current distribution, a better impedance matching, and an enhanced impedance bandwidth. Moreover, a higher gain is obtained for the disk. A design sample for fl  = 2.45 GHz and fh  = 5.3 GHz on an FR4 substrate was fabricated. Simulated and measured results agree satisfactorily. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:268–276, 2016.